2013
DOI: 10.3389/fphys.2013.00332
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells in sports: effects of exercise and training on oxygen supply by red blood cells

Abstract: During exercise the cardiovascular system has to warrant substrate supply to working muscle. The main function of red blood cells in exercise is the transport of O2 from the lungs to the tissues and the delivery of metabolically produced CO2 to the lungs for expiration. Hemoglobin also contributes to the blood's buffering capacity, and ATP and NO release from red blood cells contributes to vasodilation and improved blood flow to working muscle. These functions require adequate amounts of red blood cells in cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
329
0
25

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(363 citation statements)
references
References 171 publications
(240 reference statements)
9
329
0
25
Order By: Relevance
“…SS 1/2 , EI max and SS 1/2 to EI max ratio were reported as means ± standard deviations (SD). The methodology of analysis was previously described in detail (BASKURT & MEISELMAN 2004, 2013BASKURT et al 2009). Statistical significance was defined as P#0.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SS 1/2 , EI max and SS 1/2 to EI max ratio were reported as means ± standard deviations (SD). The methodology of analysis was previously described in detail (BASKURT & MEISELMAN 2004, 2013BASKURT et al 2009). Statistical significance was defined as P#0.05.…”
Section: Resultsmentioning
confidence: 99%
“…The degree and direction of changes in the blood morphology are determined by the characteristics of physical exercise (type, load, duration and number of repetitions) and the athlete's characteristics (age, sex, training experience) (KELLY 2005et al, KOCHANSKA-DZIUROWICZ 2007et al, ROMAIN 2011MAIRBÄURL 2013). Erythrocyte and leukocyte counts reflect the changes in plasma volume and immunological processes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As a reaction to several days of aerobic exercise, plasma volume increases and hemoglobin and packed cell volume decrease on a long term basis. Mairbaurl (2013) [21] reported that the diverging results in the studies on Hb and training are due to the different duration of exercise training. Schmidt and Prommer, (2008) [22] concluded that adjustments of Hb by training are slow, and that a pronounced increase may require several years of training.…”
Section: Discussionmentioning
confidence: 99%
“…Em virtude disto, há um aumento considerável no hematócrito, além de uma elevação na concentração de hemácias, hemoglobina e indicadores da resposta imune, ou seja, alteração da hemoconcentração resultante da redução plasmática (Mairbaurl, 2013;Tsampoukos, Stokes, & Nevill, 2014).…”
Section: Resposta Hematológica Ao Teste Máximo | 43unclassified